METHODOLOGICAL RECOMMENDATIONS FOR USING THE METHOD OF WORK IN SMALL GROUPS - Sobirova Robia Muhammadismoilovna, Botirova Palina Hakimjonovna, Inomiddinova Dildora Ikramovna (International Journal of Advanced Science and Technology, 2019)
In the present article methodical recommendation on using the method of working in small groups have been reflected, as working in small groups enables the student to develop the skills of cooperation and teach them to solve occurring compromises.